2015
DOI: 10.5751/es-07368-200151
|View full text |Cite
|
Sign up to set email alerts
|

What role can information play in improved equity in Pakistan’s irrigation system? Evidence from an experimental game in Punjab

Abstract: ABSTRACT. The Indus Basin Irrigation System suffers significant inequity in access to surface water across its millions of users. Information, i.e., monitoring and reporting of water availability, may be of value in improving conditions across the basin, and we investigated this via an experimental game of water distribution in Punjab, Pakistan. We found evidence that flow information allowed players to take more effective action to target overuse, and that overall activities that might bring social disapprova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…1). The spatially explicit positioning of the agents has parallels to lab and field experiments that have explored the differences in water-use decisions of upstream and downstream irrigators (D'Exelle et al 2012;Bell et al 2015).…”
Section: Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The spatially explicit positioning of the agents has parallels to lab and field experiments that have explored the differences in water-use decisions of upstream and downstream irrigators (D'Exelle et al 2012;Bell et al 2015).…”
Section: Experiments Designmentioning
confidence: 99%
“…Similarly, provision of information that the level of pollution in a water body is low could encourage some farmers to forgo expensive pollution-abatement activities. In irrigation games, Bell et al (2015) found that upstream players in the Indus Basin, whose water supply was unaffected by scarcity, did not change their competitive behavior in response to information that downstream players were not receiving adequate water. In contrast, D'Exelle et al (2012) found that upstream irrigation players in Tanzania played cooperatively for enabling equitable sharing of water resources between upstream and downstream players.…”
Section: Behavioral Implicationsmentioning
confidence: 99%
“…But more information sharing does not necessarily lead to the sustainable or fair use of a resource. Li (2014) provides an example of information improving the sustainable management of a groundwater resource, while Bell (2015) presents an example of the monitoring of a water resource in Pakistan leading to a decrease in water use but no improvement in equitable water distribution.…”
Section: Information Sharing For the Management Of Collective Naturalmentioning
confidence: 99%
“…Research on global common goods has pointed out the fact that information can be considered to be a common good, emphasizing the difference between information, artifacts and facilities (Hess and Ostrom, 2003). Other research on information in the context of commons management has shown its importance, for instance through studies of the effects of information availability and granularity for conditional cooperation (Villena and Zecchetto, 2010;Janssen, 2013;Bell et al, 2015). Information can be shared one-to-one (Bodin and Crona, 2009) or with groups of people during meetings or through information sharing artifacts (Allen and Kilvington, 2005;Pahl-Wostl, 2005).…”
Section: Information Sharing To Legitimize Stewardship Over Water Quamentioning
confidence: 99%